Polyvinylalcohol/Polyethyleneimine Hydrogels: Evaluation of Swelling, Dehydration and Antibacterial Activity - Emel Tamahkar Irmak; Bengi Özkahraman; Gülşen Bayrak; Işık Perçin Demirçelik; Zeynep Ciğeroğlu; Filiz Boran (Hittite Journal of Science and Engineering)

(untitled)
In the present study, Polyvinylalcohol/polyethyleneimine (PVA/PEI) hydrogels designed with different Glutaraldehyde (Glu) amount, PEI amount and PVA concentration were synthesized via solvent casting technique. The fabricated PVA/PEI hydrogels with different compositions were evaluated for swelling rate, dehydration properties and antibacterial activity to determine superior combination. The swelling tests were performed for 0-300 min at pH 7.4 and 37 °C. All of the prepared PVA/PEI hydrogels swelling ratio were observed in the range of 221-321%. The highest dehydration rate was found for the PVA/PEI hydrogel with the lowest PVA concentration and the lowest dehydration rate was found for the PVA/PEI hydrogel with the highest Glu amount. All the PVA/PEI hydrogels demonstrated high antibacterial activity against E.coli. PP5 (prepared with 5% PVA, 0.5 mL PEI and 30 µL Glu) was determined as the selected hydrogels with optimized characteristics in respect to swelling, dehydration and antibacterial activity data. This study highlights potential usage of the resultant PVA/PEI hydrogels as antibacterial wound dressings in wound care applications.